Analytical methods for food additives - Wood, Roger, 1945- (CRC Press ; Woodhead Pub., 2004)
The accurate measurement of additives in food is essential in meeting both regulatory requirements and the need of consumers for accurate information about the products they eat. Whilst there are established methods of analysis for many additives, others lack agreed or complete methods because of the complexity of the additive or the food matrix to which such additives are commonly added. Analytical methods for food additives addresses this important problem for 26 major additives. In each case, the authors review current research to establish the best available methods and how they should be used. The book covers a wide range of additives, from azorubine and adipic acid to sunset yellow and saccharin. Each chapter reviews the range of current analytical methods, sets out their performance characteristics, procedures and parameters, and provides recommendations on best practice and future research. Analytical methods for food additives is a standard work for the food industry in ensuring the accurate measurement of additives in foods. Discusses methods of analysis for 30 major additives where methods are incomplete or deficientReviews current techniques, their respective strengths and weaknessesDetailed tables summarising particular methods, statistical parameters for measurement and performance characteristics.
Keywords: Food additives -- Analysis.; elektronické knihy; electronic books